Open Microsurgical Cerebral Aneurysm Treatment After Failed Endovascular Therapy: An Evaluation of Aneurysm Treatment Frequencies in All Neurovascular Centers Across Austria and the Czech Republic Over 20 Years - Griessenauer, Christoph J; Dodier, Philippe; Stroh, Nico H; Mercea, Petra A; Bavinzski, Gerhard; Dorfer, Christian; Rössler, Karl; Gruber, Andreas; Gmeiner, Matthias; Thomé, Claudius; Leber, Klaus A; Wolfsberger, Stefan; et al. (Neurosurgery, 2024)
BACKGROUND AND OBJECTIVES: Endovascular treatment of cerebral aneurysms has tremendously advanced over the past decades. Nevertheless, aneurysm residual and recurrence remain challenges after embolization. The objective of this study was to elucidate the portion of embolized aneurysms requiring open surgery and evaluate whether newer endovascular treatments have changed the need for open surgery after failed embolization. METHODS: All 15 cerebrovascular centers in Austria and the Czech Republic provided overall aneurysm treatment frequency data and retrospectively reviewed consecutive cerebral aneurysms treated with open surgical treatment after failure of embolization from 2000 to 2022. All endovascular modalities were included. RESULTS: On average, 1362 aneurysms were treated annually in the 2 countries. The incidence increased from 0.006% in 2005 to 0.008% in 2020 in the overall population. Open surgery after failed endovascular intervention was necessary in 128 aneurysms (0.8%), a proportion that remained constant over time. Subarachnoid hemorrhage was the initial presentation in 70.3% of aneurysms. The most common location was the anterior communicating artery region (40.6%), followed by the middle cerebral artery (25.0%). The median diameter was 6 mm (2-32). Initial endovascular treatment included coiling (107 aneurysms), balloon-assist (10), stent-assist (4), intrasaccular device (3), flow diversion (2), and others (2). Complete occlusion after initial embolization was recorded in 40.6%. Seventy-one percent of aneurysms were operated within 3 years after embolization. In 7%, the indication for surgery was (re-)rupture and, in 88.3%, reperfusion. Device removal was performed in 16.4%. Symptomatic intraoperative and postoperative complications occurred in 10.2%. Complete aneurysm occlusion after open surgery was achieved in 94%. CONCLUSION: Open surgery remains a rare indication for cerebral aneurysms after failed endovascular embolization even in the age of novel endovascular technology, such as flow diverters and intrasaccular devices. Regardless, it is mostly performed for ruptured aneurysms initially treated with primary coiling that are in the anterior circulation.
Keywords: neurochirurgické výkony; Treatment Failure; Male; Endovascular Procedures; retrospektivní studie; neúspěšná terapie; Rakousko; mikrochirurgie; Česká republika; Embolization, Therapeutic; endovaskulární výkony; Adult; Aged; dospělí; mužské pohlaví; senioři; Czech Republic; Intracranial Aneurysm; senioři nad 80 let; lidé; ženské pohlaví; Microsurgery; Humans; Aged, 80 and over; Austria; Neurosurgical Procedures; terapeutická embolizace; Retrospective Studies; Female; intrakraniální aneurysma; lidé středního věku; Middle Aged